Long-Term Health-Related Quality of Life Outcomes in Digital Replantation versus Revision Amputation - Tessler, Oren; Bartow, Matthew J.; Tremblay-Champagne, Marie P.; Lin, Alex M.; Landes, Geneviève; Sebbag, Sarah; Nikolis, Andreas (Journal of Reconstructive Microsurgery, 2017)
Background Earlier, digit viability judged the success of digital replantation. Now, utility health-related quality of life (HRQOL) measures can better assess the impact of digital replantation.Methods Overall, 264 digital injury patients were sent a regimen of utility measures: Disabilities of the Arm, Shoulder and Hand (DASH) score, European Quality of Life 5 Dimensions, visual analog scale (VAS), time trade-off (TTO), and standard gamble (SG). Overall, 51 patients responded completely to all of these—36 replantation patients and 15 revision amputation patients. The utility results of these patients were stratified between replantation versus revision amputation; dominant hand replantation versus nondominant hand replantation; and dominant hand revision amputation versus nondominant hand revision amputation.Results The mean VAS score of replant (0.84) and revision amputation (0.75) groups was significantly different (p = 0.05). The mean DASH score of dominant hand replantations (29.72) and nondominant hand replantations (17.97) was significantly different (p = 0.027). The dominant hand revision amputation had higher anxiety levels in comparison to nondominant hand revision amputation (p = 0.027). Patients with two or more digits replanted showed a significant decrease in VAS, TTO, and SG scores in comparison to patients who only had one digit replanted (p = 0.009, 0.001, and 0.001, respectively).Conclusions This study suggests that HRQOL can offer better indices for outcomes of digital replantation. This shows some specific replantation cohorts have a significantly better quality of life when compared with their specific correlating revision amputation cohort. These findings can be employed to further refine indications and contraindications to replantation and help predict the quality of life outcomes.
Keywords: digital replantation; utility; hand; revision amputation